Teaching english as an international language : - McKay, Sandra Lee (Oxford University Press, 2002)
This book is An accessible overview of this increasingly important field. English is the major language of international communication, and everyone wants to learn it. But which English, and how? This book questions the cultural assumptions underlying much English teaching, and suggests classroom aims and teaching methods based on the requirements of an international language